The risk of kidney transplant graft loss in sensitized vs. unsensitized patients is modified by prior transplant status - Nicholson, A.; Tennankore, K.; Vinson, A. J. (Frontiers in Transplantation, 2026)
BackgroundA prior kidney transplant (KT) has been associated with an increased risk of graft loss following repeat transplantation. This study examined the risk of adverse posttransplant outcomes between patients with and without a prior transplant, depending on sensitization status.MethodsWe used propensity score matching to examine the combined exposure of sensitization status [panel-reactive antibody (PRA) 0%, >0%–80%, and >80%] and first/repeat KT as a nested variable in adults across the US [2000–2017; Scientific Registry of Transplant Recipients (SRTR)]. We then used multivariable Cox and logistic regression models to examine the association between the nested variable and death-censored graft loss (DCGL), all-cause graft loss (ACGL), and delayed graft function (DGF). Effect modification between PRA status (20%) and prior KT status was assessed for each outcome.ResultsAmong 38,660 matched patients, DCGL (adjusted Hazard Ratio (aHR) 1.56, 95% CI 1.47–1.66), ACGL (aHR 1.42, 95% CI 1.35–1.49), and DGF (adjusted Odds Ratio (aOR) 1.89, 95% CI 1.75–2.03) risk was highest with a prior KT and PRA >80% (vs. unsensitized transplant-naïve patients). The risk associated with increased PRA was greater in those with a prior transplant. Prior KT modified the association between increased PRA and DCGL, ACGL, and DGF (p-value < 0.001).ConclusionPrior KT status modified the association between PRA and adverse outcomes. Sensitized patients (PRA >80%) with a prior KT faced higher risks of DCGL, ACGL, and DGF compared with sensitized patients without a prior KT.